MAPPING READING QUESTIONS OF SUMMATIVE TEST FOR ELEVENTH GRADE OF SMK ST. NAHANSON PARAPAT SIPOHO - Ivan Fernando Simanjuntak; Marisi Debora (Universitas Negeri Medan, 2022)
This study aimed to analyze the distributions of the cognitive process dimensions of Revised Bloom’s Taxonomy and the distribution of indicators on reading questions of summative test. The design of this research was a descriptive qualitative study with a survey method. This research was conducted in SMK St. Nahason Parapat Sipoholon on 2020/2021 academic year. The data of this research was the reading questions of summative tests used by the teacher in the odd semester examination. The source of the data was a summative test for eleventhgrade students in the 2020/2021 academic year. The data were analyzed using Revised Bloom's Taxonomy's operational verb dimension of the cognitive process and grouped according to basic competencies and indicators in the syllabus. The findings revealed that: (1) the distribution of the cognitive process dimensions of Revised Bloom's Taxonomy on the summative reading test are not evenly distributed, and the question is dominated by the dimensions of the level process cognitive remembering (C1) and understanding (C2). The average distribution of dimensions of the cognitive process of Revised Bloom's Taxonomy on reading test was the cognitive process dimensions level C1 of 12 questions out of 18 in total (56%), C2 consist of 4 questions (22 %), C3 was not included (0 %), C4 covered 4 questions (22 %), C5 by 0 %, and C6 by 0 %. (2) The distribution of indicators on the odd semester exam questions of reading test was not evenly divided. There are 26 indicators arranged by the English teacher for odd semester, only 2 indicators are included in the reading test items for total 9 questions out of 18 in total. Some indicators are not included in the questions, and there are 9 questions (50%) out of 18 in total were not related to the indicator.Keywords: Reading Questions of Summative Test, Cognitive Process Dimension of Revised Bloom’s Taxonomy, Indicator